2002
DOI: 10.1128/iai.70.3.1547-1557.2002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Inflammatory Mediators in Resistance and Susceptibility to Pneumococcal Infection

Abstract: Variations in the host response during pneumonia caused by Streptococcus pneumoniae in susceptible (CBA/Ca) and resistant (BALB/c) inbred mouse strains were investigated. Significant differences were detected in survival time, core body temperature, lung-associated and systemic bacterial loads, mast cell numbers, magnitude and location of cytokine production, lung disruption, and ability of isolated lung cells to release the cytokine tumor necrosis factor (TNF) alpha in vitro. Overall, the results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
95
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 55 publications
(40 reference statements)
16
95
2
1
Order By: Relevance
“…This would parallel the observations made regarding the role of cytokines such as TNF-␣ in the host response to infections caused by another Gram-positive pathogen, Streptococcus pneumoniae (45,46). Clearly, overproduction of TNF-␣ and other inflammatory mediators contributes to the pathogenesis of septic shock and multiorgan failure during overwhelming pneumococcal infection.…”
Section: Discussionsupporting
confidence: 51%
“…This would parallel the observations made regarding the role of cytokines such as TNF-␣ in the host response to infections caused by another Gram-positive pathogen, Streptococcus pneumoniae (45,46). Clearly, overproduction of TNF-␣ and other inflammatory mediators contributes to the pathogenesis of septic shock and multiorgan failure during overwhelming pneumococcal infection.…”
Section: Discussionsupporting
confidence: 51%
“…A previous study reported that after intranasal pneumococcal infection, TNF-␣ receptor KO mice exhibit elevated bacteremia and progress more rapidly to a fatal outcome (12). Although studies showed that TNF-␣ may be dispensable in pulmonary responses, it appears to be a necessary beneficial regulator of systemic organ protection in pneumococcal disease (15).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies showed that TNF-␣ may be dispensable in pulmonary responses, it appears to be a necessary beneficial regulator of systemic organ protection in pneumococcal disease (15). The role of TNF-␣ may be a double-edged sword, since TNF-␣ is important in the early stages of infection but its levels need to be controlled later to avoid an exacerbated inflammatory response (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether human mast cells interact with the pneumococcus is unknown. However, we previously showed more mast cells in the airways of mice that successfully cleared pneumococci from their lungs following intranasal infection compared with those that did not (32).…”
mentioning
confidence: 90%